Neofinalism - Ruyer, Raymond, 1902-1987 (Posthumanities, 2016)
Although little known today, Raymond Ruyer was a post-WWII French philosopher whose works and ideas were significant influences on major thinkers, including Deleuze, Guattari, and Simondon. With the publication of this translation of 'Neofinalism, ' considered by many to be Ruyer's magnum opus, English-language readers can see at last how this seminal mind allied philosophy with science. Unfazed by the idea of philosophy ending where science began, Ruyer elaborated a singular, nearly unclassifiable metaphysics and reactivated philosophy's capacity to speculate on its canonical questions: What exists? How are we to account for life? WHat is the status of subjectivity? And how is freedom possible?